Source to sink wastewater surveillance of severe acute respiratory syndrome Coronavirus-2 (SARS-CoV-2) for COVID-19 monitoring. - Folkes, Miles George Terence (Cranfield University, 2022)
Wastewater-based surveillance (WBS) complements individual testing to assess disease burden within geographically defined communities. Here, the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) RNA fragments of N1 and E genes were monitored intermittently over ~16-month period (19th March 2020 – 21st July 2021) from large buildings on a university campus (near-source), in-sewer, raw wastewater and treated effluents to monitor infection burden within a small University in England, United Kingdom. SARS-CoV-2 abundance positively correlated with ammonia at near-source (Spearman’s Rank; ρ(14) = 0.82, p < 0.01) and at the in-sewer (Spearman’s Rank; ρ(26) = 0.54, p < 0.01) spatial scales but not within the onsite wastewater treatment works (WWTW) inlet or treatment process interstage samples. Campus infections and detection of SARS-CoV-2 RNA in wastewater occurred consistently through the survey and increasing trends lagged local area infection data and community cases of emerging / dominant variants of concern. Sequencing of the SARS-CoV-2 genomes from wastewater suggested detection of Alpha (B.1.1.7) Variant of Concern from wastewater samples. The University secondary WWTW (roughing and nitrifying trickling filters) did not removal substantial quantities of SARS-CoV- 2 and the virus was regularly detected in permitted discharges, despite complete compliance to conventional wastewater consents during the survey. Although the virus was detected, there is very strong confidence in it not being active and thus it is not infectious. Remote and rural WWTW may not be effective at breaking down the RNA of enveloped viruses such as SARS-CoV-2 prior to discharge. In conclusion SARS-CoV-2 WBS can be used to proactively manage the health of campus-based communities as a complimentary measure of health status. Testing WBS at near-source, in-sewer and interstage WWTW provides the first single source to sink surveillance program to support broader roll out of WBS as a surveillance method.
Keywords: wastewater surveillance; wastewater-based epidemiology (WBE); surveillance COVID-19; SARS-CoV-2; coronavirus; Pepper mild mottle virus (PMMoV)